ANALISIS KEBIJAKAN ALIH FUNGSI LAHAN PERTANIAN TERHADAP KETAHANAN PANGAN DI KOTA PROBOLINGGO TAHUN 2021 - Imam Sucahyo; Verto Septiandika; Boby Maulana (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Bhayangkara Surabaya, 2022)
Probolinggo City is one of the north coast cities where this city is a transit city. With this, making this city a transit city and increasing the number of immigrants due to development from an economic perspective, this has resulted in many conversions of agricultural land functions into residential and industrial areas, every year the City of Probolinggo experiences conversion of agricultural land reaching 25-40 hectares per year. With that it is necessary to prevent the conversion of agricultural land in Probolinggo City. This type of research is descriptive qualitative, namely research that intends to describe or describe a situation or event. From the results of the research that has been done, there is a decrease in the amount of agricultural land in Probolinggo City. The decrease in the amount of agricultural land in Probolinggo City was caused by the land owners themselves and external needs such as the construction of housing and other infrastructure.